Academic Gratitude as a Mediator between Psychological Well-Being and Academic Buoyancy among college students in West Java - Wardhani, Nurul; Agustiani, Hendriati; Hutasuhut, Ida Juliana; Siswadi, Ahmad Gimmy Prathama (Frontiers in Psychology, 2026)
IntroductionThis study aims to examine the relationships among Psychological Well-Being, Academic Gratitude, and Academic Buoyancy among students in Indonesia, and to assess whether Academic Gratitude acts as a partial mediator in these relationships.MethodsA total of 407 students (304 females and 103 males) participated in an online survey, selected via stratified random sampling by academic year. The data were analyzed using a covariance-based structural equation model (SEM).ResultsThe results showed that Psychological Well-Being was positively related to Academic Gratitude and Academic Buoyancy, while Academic Gratitude was also positively related to Academic Buoyancy. Mediation analysis using bootstrapping with 5,000 resamples showed that Academic Gratitude partially mediates the relationship between Psychological Well-Being and Academic Buoyancy, suggesting that gratitude functions as an affective-cognitive pathway that explains the interrelationships among the three constructs.DiscussionGiven the cross-sectional nature of the study design, the direction of the relationship cannot be concluded as causal and requires further examination in longitudinal or experimental studies. Overall, these findings provide empirical support for the role of gratitude in understanding student adaptation to academic challenges in the context of higher education in Indonesia.